Diseño de un manual de higiene, salud y seguridad ocupacional para el personal de la cooperativa de ahorro y crédito andina, período 2012-2013 - Gallegos Tapia, Byron Iván (2013)
The present research is done with the need for a Manual of hygiene, health and safety for the staff of the Credit Cooperative Andina. It is important to implement manual, safe procedures which carry out preventive rules for worker safety. Research Group conducted the analysis of the risks that exist in Union and Andean Credit, collected information from rules, laws and national regulations for the prevention and management of risks, with these contents made a manual that can be executed within the institution for all functions played by the staff and thus minimize the possible conditions to your health and that all existing dangers can be avoided.